2015
DOI: 10.1002/14651858.cd008351.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Airway clearance techniques for bronchiectasis

Abstract: Analysis 2.1. Comparison 2 Stable bronchiectasis: chest physiotherapy ACT vs no ACT (control), Outcome 1 Change in HRQoL..... Analysis 2.2. Comparison 2 Stable bronchiectasis: chest physiotherapy ACT vs no ACT (control), Outcome 2 Change in FEV1....... Analysis 2.3. Comparison 2 Stable bronchiectasis: chest physiotherapy ACT vs no ACT (control), Outcome 3 Change in FVC........ Analysis 2.4. Comparison 2 Stable bronchiectasis: chest physiotherapy ACT vs no ACT (control), Outcome 4 Change in TLC........ Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 111 publications
0
94
0
12
Order By: Relevance
“…24,25 It is thus vital to achieve early identification of bronchiectasis and initiate evidencebased therapies that have been shown to slow the rate of lung function decline or improve quality of life. 9,10 Twiss et al 25 guideline recommends "regular" review which is defined as "at least an annual review in adults" and "6-monthly review in children". 1 Given the findings of our study, these recommendations may not meet the requirements for the burden of illness bronchiectasis patients have.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 It is thus vital to achieve early identification of bronchiectasis and initiate evidencebased therapies that have been shown to slow the rate of lung function decline or improve quality of life. 9,10 Twiss et al 25 guideline recommends "regular" review which is defined as "at least an annual review in adults" and "6-monthly review in children". 1 Given the findings of our study, these recommendations may not meet the requirements for the burden of illness bronchiectasis patients have.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects with CF were seen by a respiratory physician at least three times in the calendar year analyzed. By comparison, subjects with bronchiectasis had far fewer visits, median (range) 5.5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) (13). By comparison the mean (SD) number of inpatient physiotherapy consults for admitted patients with CF was greater at 21 (9) but the difference was not statistically significant (P = .31).…”
Section: Respiratory Physician Appointment Frequency and Physiothermentioning
confidence: 90%
See 1 more Smart Citation
“…In a Cochrane review done in 2015, on ACT in bronchiectasis, looking at seven studies, of which only one included children, studies show significant improvement in QOL with no safety issues (38). …”
Section: Possible Treatment Determinants Of Qolmentioning
confidence: 99%
“…The core components involve postural drainage, percussion, vibration of the chest wall, and coughing (96), and specific techniques include active cycle of breathing techniques, forced expiration techniques, autogenic drainage, postural drainage, oscillating positive expiratory pressure, high frequency chest wall oscillation, and exercise and/or pulmonary rehabilitation (96). While a Cochrane review found these techniques have clinically important effects on health-related QoL scores in adults (97), it identified only one study in children with bronchiectasis (98). This study involved only nine children with bronchiectasis and the intervention was oscillatory positive expiratory pressure administered three times a day with lung function measured after a 3-month period.…”
Section: Preventionmentioning
confidence: 99%